Study Of Risk Factors For Candida Species Colonisation Of Neonatal Intensive Care Unit Patient - DR. ARUN KUMAR,; DR. APARNA YADAV,; DR. GEETA GATHWALA,; DR. DEEP GAGNEJA,; DR.UMA CHAUDHARY,; DR. P.S.GILL, (International Journal of Pharma and Bio Sciences, 2012)
Purpose : Candida spp. are increasingly important pathogens in neonatal intensive care units (NICU). Prior colonisation is a major risk factor for candidemia, but few studies have focused on risk factors for colonisation, particularly in NICU patients Methods: A prospective study was performed in NICU to determine risk factors for Candida colonisation. Sample of blood was taken and swabs from various body sites were collected on day 0 (within 24 hrs. of birth), 48 ± 12 hrs., 72 ± 12 hrs., postnatal day 5, postnatal day 7 and once weekly thereafter till and were cultured . Results: The prevalence of Candida spp. colonisation was 27.5% (302 of 1098 neonates). Of 639 isolates, 50.23% were of C. albicans followed by 31.14% of C. tropicalis, 6.4% of C. glabrata and 12.2% of C. parapsilosis. Use of central venous catheters, multiple antibiotics, endotracheal intubation were risk factors for development of colonisation whereas delivery by caesarean section was protective. Conclusions: We speculate that in NICU patients, use of multiple antibiotics, steroids and IV catheters alter ecology of all body systems, thereby facilitating colonisation of Candida spp.